Tomorrow’s Green Buildings: Optimum Natural Insulation Material Modeling - Sua, Lutfu S.; Balo, Figen; Ucar, Ukbe (Springer Verlag, 2020)
The structures renovation’s economical impact generally relies on the devices and energy-saving methods’ application. By wall insulation, great economical impact is accomplished. In this regard, it is even greater than changing the windows. The wall insulation option resolutions of structures vary in the materials utilized, labor force spending, and other ways. The renovation’s cost based on the resolutions applied. The criteria describing the existing wall isolation options may have diverse values. Additionally, they may differ in diverse instructions, i.e., a greater value of some criteria represents a preferable situation, while for others they signify a worse state. By means of multicriteria assessment methodologies, a reconciliation variable is needed, which can be obtained in this environment. To decrease the impact of diverse methodologies on computational conclusions, it can be proposed to evaluate the phenomenon (or object) thought by a few diverse methodologies, with the detection of the average forecast value. Thus, the several special multicriteria assessment methodologies’ disadvantages could be replaced by the others’ benefits. In recent years, thermal insulation materials’ many styles are present in the market. The calculations made in this study by AHP multicriteria assessment methodology allowed us to determine the most effective insulation material option out of ten used alternatives commercial insulation materials. In the second stage, the most assessable natural alternative insulation material among ten different uncommercial-natural insulation materials is analyzed with the same methodology. © 2020, Springer Nature Switzerland AG.
Keywords: Green building; Green insulation; Mathematical modeling; Natural insulation material